Carrying Angle And Its Correlation With Height In Central Indian Paediatric Population - Mishra, Yatharth; Bamne, Avantika; Bharti, Abhishek; Gaur, Parul (Journal of Neonatal Surgery, 2025)
Introduction: Carrying Angle (CA) is formed between long axis of arm and forearm when arm is supinated and elbow joint is fully extended leading to lateral deflection of forearm. In healthy growing children the range of elbow joint motion and CA increases with age until skeletal maturity, increasing up to 15 years thereafter decreasing slightly. Effect of increasing height on CA at elbow has not been extensively studied in paediatric population creating a void. Aims & Objective: Present study finds out correlation between height and CA in paediatric population. Objectives were to identify gradual variation in CA according to height variation in children as their age advanced. Material & Method: Five hundred four (504) children of both sexes aged 6-14 years, grouped in four groups [I, II, III and IV] were assessed for CA using manual goniometer while height was measured using stadiometer. Statistical calculations were done using Prism software. Result: Present study reports a positive correlation between CA and height as the CA increased gradually in all the four groups with increasing height from group I to group IV. Discussion & Conclusion: This study demonstrates the positive correlation of CA with height in paediatric population irrespective of gender. Apparently present is the only study till date showing gradual CA increase with advancing height according to age in children (6-14 years) undergoing active skeletal growth and maturation period. Clinical Relevance: Knowledge of CA and its variation is important anatomic feature assisting orthopaedic surgeons in management of elbow fractures, restoration, implants, and other diseases. It may be useful for forensic anthropologists in assessing skeletal remains.